Investigation of Potential ofOxalis corniculata Through Inhibition of Matrix Metalloproteinases for the Treatment of Skin Photoageing: An in silico Approach - Baghel, Madhuri; Bhargav, Sushil (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: O. carniculata contains bioactive substances called C-glycosyl-flavones that have antioxidant and anti-inflammatory properties. The inhibitory effect of C-glycosyl-flavones of O. carniculata on MMPs was established by in silico molecular modeling approach, that are linked to the collagen degradation pathway. Materials and Methods: Structural flexibility, binding-conformation, binding-free energy, and protein-ligand-interaction profile of Matrix Metalloproteinases (MMPs): MMP1 (966C), MMP3 (1G4K), and MMP9 (1GKC) were established using molecular docking, induced fit docking and pharmacophore mapping to understand the structural basis of three C-glycosyl-flavones, viz Isoorientin (6-C-glucosyl-lutein), Isovitexin (6-C-glucosyl-apigenin) and Swertisin (7-methylether-isovitexin), for their potential as MMP inhibitor. Additionally, the e-pharmacophore model for MMP inhibitors has been developed in a way that efficiently mapped all of the crucial pharmacophoric attributes associated with the MMP inhibitory activity. Results and Discussion: Isoorientin and Isovitexin showed the greatest binding affinity to the MMPs among the three C-glycosyl-flavones. The e-pharmacophores had three (for 966C) and, six (for 1G4K and 1GKC) featured models and all showed good fitness score (ranging from 1.42 to 1.49) These results demonstrate that the Isoorientin has the greatest potential for use as an anti-skin-aging agent with the MMP inhibitory activity.
Keywords: MMP; Molecular docking; Phytochemicals; Induced fit docking; Pharmacophore